Flipping Subscription and Access Fees to Perpetuity. Issue 3 (2nd October 2021) - Rodriguez, Michael
Abstract: Seeking to maximize budgetary efficiency and safeguard important resources from future budget reductions, the UConn Library collaborated with vendors to buy out its subscription and access fees, flipping the model from leased to perpetual access. Striving for sustainable stewardship of its collections, the Library achieved 125, 000 in cost savings—equivalent to approximately 2.5% of its collections budget and 10% of its budget line items. This column explains how we did it.